Efficacy of travel management areas for reducing disturbance to mule deer during hunting seasons - Angelique M. Curtis; Johan T. Du Toit (Wildlife Society Bulletin)
ABSTRACT For 50 years, the Oregon Department of Fish and Wildlife, USA, has designated travel management areas (TMAs) in which certain roads are closed to motorized traffic during hunting seasons with the goal of reducing disturbance to mule deer (Odocoilius hemionus). The efficacy of TMAs has not been tested. We measured the effects of temporary road closures on mule deer locations during the 2015 hunting season in 2 TMAs in eastern Oregon. We used data collected during 1 August–31 October 2015 from female mule deer (n = 90) fitted with Global Positioning System (GPS) transmitters programmed for a 13‐hr fix interval. Euclidean distance to the nearest “closed” and “open” road was measured for each GPS location. Our results for Murderers Creek–Flagtail and Camp Creek TMAs were mixed but opposite to our predictions. Locations of deer that were nearer to open roads than closed roads were more frequent than expected for both TMAs. Mean distance from a deer location to a closed road was less than to an open road in both TMAs (85% less in Camp Creek and 21% less in Murderers Creek–Flagtail) but then in both cases, mean distance to any road (closed or open) was >2× greater inside the TMA than outside. Our results found no consistent effect of temporary demarcations of road closures in the TMAs. Management recommendations include designating a more even balance of closed and open roads for statistically improved monitoring of TMA efficacy, better enforcement of road closures during hunting seasons, and better demarcation (signage) of both closed and open roads in each TMA. © 2017 The Wildlife Society.